Pemupukan Jelutung Rawa (Dyera pollyphylla Miq. Steenis) dengan Menggunakan Pupuk Dari Ekskresi Walet: Fertilization of Swamp Jelutung (Dyera pollyphylla Miq. Steenis) Using Fertilizer from Swallow Excrement - Lendra, Kristova; Rosdiana, Rosdiana; Tanduh, Yusintha; Dwiastuti, Rini; Nursiah, Nursiah (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
This research aims to analyze the application of swallow excrement fertilizer on the growth of swamp jelutung (Dyera pollyphylla (Miq.) Steenis) and determine the optimal dosage of swallow excrement fertilizer for swamp jelutung (Dyera pollyphylla (Miq.) Steenis). The study was conducted in 2021, observing plant height, diameter, and leaf count over a period of 2 months. The research design method used was a Randomized Complete Block Design (RCBD). The study took place in the Green Campus area of UPR, located on Yos Sudarso Street, as part of the Seedling Garden (Kebun Benih Semai or KBS) planting area, in collaboration with BPDAS-HL Kahayan and Palangka Raya University. The results of the research indicate that the growth of swamp jelutung plants in the open area (Y3 - 100 gr/plant) showed the highest average growth, while in the closed area, the highest average growth was observed in treatment Y4 (150 gr/plant) with an average height of 31.20 cm. The increase in the diameter of swamp jelutung plants in the open area with treatment Y4 (150 gr/plant) showed the largest average value, which is 14.3 cm. Similarly, in the closed area with the same treatment (Y4 - 150 gr/plant), the average diameter was 14.4 cm. The increase in the number of leaves in the open area with treatment Y150 showed an average value of 1857 leaves, while in the closed area with the same treatment (Y150), the average number of leaves was 2136